2014
DOI: 10.1097/mca.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the serum alkaline phosphatase level and the severity of coronary artery disease

Abstract: Elevated ALP levels are associated with higher Gensini scores and a more severe form of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 3 publications
2
24
0
1
Order By: Relevance
“…ALP has been associated with the outcomes and prognoses of patients with cardiovascular disease and peripheral artery disease [8][9][10], and a study of 2029 acute stroke patients found that the mortality risk of patients with ALP levels>97 U/L was almost three times greater than that of those with ALP levels<57 U/L [17]. This difference is likely related to vascular smooth muscle calcification, which results in arteriosclerosis and precedes a series of brain impairments, including ischemic cerebral stroke, leukodystrophy, and intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALP has been associated with the outcomes and prognoses of patients with cardiovascular disease and peripheral artery disease [8][9][10], and a study of 2029 acute stroke patients found that the mortality risk of patients with ALP levels>97 U/L was almost three times greater than that of those with ALP levels<57 U/L [17]. This difference is likely related to vascular smooth muscle calcification, which results in arteriosclerosis and precedes a series of brain impairments, including ischemic cerebral stroke, leukodystrophy, and intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Non-tissue specific ALP is expressed in various organs, including the liver, kidneys, and bone, and plays an important role in clinical diagnoses. For example, ALP levels are associated with the outcomes and prognoses of patients with cardiovascular disease and peripheral artery disease [8][9][10], and there is an association between ALP levels and lacunar infarctions. However, few studies have investigated the association between ALP and cognitive function in patients with SIVD.…”
Section: Biomedical Research 2018; 29 (1): 149-154mentioning
confidence: 99%
“…These results have led to a focus on ALP in patients with CAD. Sahin et al showed that elevated ALP levels are associated with high Gensini scores and a more severe form of CAD (11) . However, whether ALP is associated with the extent and severity of CAD in AMI patients was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…High serum ALP levels are an independent predictor of mortality, AMI, and stent thrombosis in CAD patients after percutaneous coronary intervention (PCI) with drug-eluting stents (10) . Elevated ALP levels were associated with more advanced forms of CAD in patients with stable angina pectoris (11) . To the best of our knowledge, the relationship between ALP and extent and severity of CAD in patients with AMI has not been evaluated previously.…”
Section: Introductionmentioning
confidence: 99%
“…From the cardiovascular standpoint, ALP is best known for hydrolyzing pyrophosphate, an inhibitor of vascular calcification (1). Several reports have linked plasma ALP levels to adverse cardiovascular events: all cause and cardiovascular mortality (1); risk of mortality and of hospitalization (2); coronary heart disease risk (3); mortality, myocardial infarction and stent thrombosis after coronary angioplasty (4); severity of coronary artery disease (5).…”
Section: Introductionmentioning
confidence: 99%